Table of Content - - (Journal of Educational and Psychological Sciences, 2025)
Table of Content: • The Social Intelligence Level of School Teachers in East Jerusalem: An Administrative Perspective from Principals and Vice Principals Ms. Rula Nemir Faries Ganem Khatib, Ms. Bayan Ali Muhammad Awar • The Predictive ability of Mindfullness in Burnout among inclusive schools Teachers in Alkarak Governorate Ms. Asmaa Abdelwahab Alkhtatnah, Asst-Prof. Mikail Ibrahim • Psychological Resilience and Its Relationship with Some 21st Century Skills Among Students of the Education Department at the University of Nizwa Asst-Prof. Nasser Sulaiyam Almazidi , Asst-Prof. Khulood Ahmed Alobaidania • The Effectiveness of Rational Emotional Counseling Program in Reducing the Depressive Symptoms Among Retired Individuals in Salfeet Governorate Co-Prof. Mona Abdel Qader Belbeisi, Mr. Alaa Abdel Hakim Muhammad Ibrahim • The Impact Level of Post-Traumatic Stress Disorder (PTSD) Symptoms on the Psychological and Behavioral Health of Students at the University of Sharqiyah in the Sultanate of Oman Dr. Khulood Ahmed Al-Obaidani, Ms. Khawla Salim Al-Habsi • The Sensorimotor Pathway to Musical Development in Early Childhood: Critical Theoretical Review of Educational Progress (2015–2025) Mr. Hassan Zrhida